Contribuições da gamificação, enquanto metodologia ativa de aprendizagem, para o processo de ensino e aprendizagem de matemática - VIDAL, Claudecy Welyton Correa (2025)
In the current scenario of Brazilian education, it has become evident the need to apply new ways of promoting mathematical learning, even though in some cases traditional didactics can be considered efficient, still persist students with great difficulties in the construction of their mathematical knowledge. Taking into account this problem, this work is theoretical in nature and aims to investigate whether gamification, as an Active Learning Methodology, contributes to the process of teaching and learning Mathematics. As the forms of active methodologies are broad, gamification was selected as a focus among the other structures, which has gained visibility for its ability to create meaningful experiences when applied in contexts of everyday life. The results show that the use of gamification as a teaching tool arouses greater interest of students. In addition to providing students with the development of other skills in the construction of their knowledge, through the experiences experienced in the classes.